O ensino e aprendizagem da língua portuguesa de crianças com surdez no período de alfabetização - Almeida, Rosimeri Maria dos Santos (2022)
This research aims to investigate Portuguese language teaching and learning process towards children with deafness within their literacy period, as well as its implications for their writing and reading acquisition. Its theoretical background is based on the theory of utterance presented by Mikhail Bakhtin and the Circle ([1929] 1992), on Vygotsky's socio-historical approach to learning (1983-1991) and the ideas and contributions of Paulo Freire's sociocultural perspective. This study comes from a process of reflection and analysis of reality. Therefore, it is based on a qualitative approach, which, according to Oliveira (2013), uses methods and techniques to understand its subject of study within a given historical context. The research investigated deaf children enrolled in the public system of regular education in the city of Várzea Grande-MT who have received specialized education for deafness at the Center for Care and Support for Inclusion João Ribeiro Filho. All participants were involved in Portuguese and Libras literacy process, except for one, who was prevented from learning Libras. The study investigates the challenges deaf people face when they develop Portuguese Language writing or reading skills. Results showed that, just as hearing children, children with deafness create their own hypothesis to spell Portuguese words. Although some of them develop syllabic-alphabetical writing level, none of them uses sound correspondence to write letters, syllables and words. So, writing and reading are developed through memory. When starting formal language study at regular schools, children with deafness are submitted to oral methodologies, once they do not have a structured language, which give them a sense of belonging. Thus, research results lead us to conclude that children with deafness use Libras to scaffold Portuguese language learning. We emphasize that the research suffered interferences due to the pandemic caused by the new coronavirus, so it has been rethought and restructured within the educational models used over this period. Our research was accepted by the National Research Ethics Committee – CONEP in May 2021.